Applying sustainability indicators to eco-tourism development: the case of Jeram Linang Amenity Forest, Kelantan - Jabil Mapjabil,; Mazdi Marzuki,; Rosmiza Mohd Zainol,; Ahmad Tharmizzie Mat Jusoh,; Ruzannna Syamimi Ramli, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Sustainability is key to any long term eco-tourism development and particular performance indicators may be developed and applied to monitor the sustainable development of unique eco-tourism attractions. Jeram Linang Amenity Forest is unique in its scenic waterfalls, flora and fauna, and elevated river flows. This study examined the level of sustainable development of this Kelantan’s eco-tourism resource based on visitors’ perceptions of sustainable indicators set by the World Tourism Organisation (WTO). A total of 140 respondents participated in this study. The study found waste dumping as a major problem in this amenity forest where the littering by irresponsible visitors had lead to the destruction of its beautiful scenery. Open burning within the area vicinity was also found to be undermining the pristine state of the forest despite its being a protected area under the jurisdiction of Ulu Sat Forest Reserve. All this point to the imperative of well planned and well executed remedial actions involving all stakeholders.